Respuesta :
Answer:
Hey there!
3(a+b)-2(2a-b)+4a-7a
3a+3b-4a+2b-3a
3b-4a+2b
5b-4a
-4a+5b
Let me know if this helps :)
Answer
[tex] \boxed{ \boxed{ \bold{ \red{ - 4a + 5b}}}}[/tex]
Step by step explanation
[tex] \sf3(a + b) - 2(2a - b) + 4a - 7a[/tex]
Distribute 3 through the parentheses
⇒[tex] \sf3a + 3b - 2(2a - b) + 4a - 7a[/tex]
Distribute 2 through the parentheses
⇒[tex] \sf3a + 3b - 4a + 2b + 4a - 7a[/tex]
Collect like terms
⇒[tex] \sf3a +4a - 4a - 7a + 3b + 2b[/tex]
Since , two opposites add up to zero, remove them from the expression
⇒[tex] \sf3a - 7a + 3b + 2b[/tex]
⇒[tex] \sf - 4a + 5b[/tex]
Hope I helped!
Best regards!!